Age‐related cognitive decline is accelerated in alcohol use disorder - Kazuhiro Kurihara; Ayano Shiroma; Munenaga Koda; Hotaka Shinzato; Yoshikazu Takaesu; Tsuyoshi Kondo (Wiley, 2023)
Abstract This study aimed to examine potential cognitive impairments in patients with alcohol use disorder (AUD), and explore the factors affecting them. We recruited 97 inpatients with AUD, showing superficially normal cognitive function (mini‐mental state examination score ≥24) for this study. We assessed cognitive function after a 4‐week post‐abstinence period using the Brief Assessment of Cognition in Schizophrenia‐Japanese version (BACS‐J). Relationships between BACS‐J subcategory/composite raw scores and Z‐scores (deviation from standard data in healthy Japanese) and background factors such as age, sex, education, smoking status, mini‐mental state examination score, body mass index, systolic blood pressure, severity of depression, alcohol consumption, and laboratory findings were analyzed. Multiple regression analysis showed that the age (p < 0.001) and total bilirubin level (p = 0.014) were worsening factors for the BACS‐J composite raw score, whereas education (p < 0.001) was a protective factor. An inverse correlation was apparent between the age and the composite Z‐score of the BACS‐J (r = −0.431, p < 0.001). Receiver operating characteristic (ROC) analysis identified 53 years as the cutoff age for predicting more than −2SD cognitive decline from the normal standard, with a high negative predictive value (95%). Patients with AUD aged ≥53 years showed more pronounced impairments in verbal memory, working memory, verbal fluency, and attention than those younger than 53 years (p < 0.05). These findings clearly demonstrate accelerated age‐related cognitive decline in patients with AUD, especially those aged ≥53 years, suggesting the necessity of early intervention in patients with AUD to prevent progressive cognitive impairment and preserve their quality of life.